The natural occurrence of toxigenic moulds and mycotoxins in Slovenian primary grain production - Breda JAKOVAC-STRAJN; Anton VENGUŠT; Igor UJČIČ-VRHOVNIK; Katarina PAVŠIČ-VRTAČ; Gabrijela TAVČAR-KALCHER (Acta Agriculturae Slovenica)
The aim of the present study was to determine the contamination of grains, grown in Slovenia and used for animal diets by Slovene farmers in year 2009. A total of 66 samples was examined on toxigenic moulds from genera Fusarium, Penicillium, Aspergillus, Alternaria and on 8 different mycotoxins. The leading contaminants among moulds were from Fusarium spp., detected in 51 samples, mostly in barley (19). The average number of Fusarium spp. colony forming units (cfu) in different grains was from 5.5-23.3 x 103/g, whereas the contamination of barley with Penicillium, Aspergillus and Alternaria spp. was 4.5, 19.3 and 5 x 103 cfu/g. Using liquid (HPLC) and gas chromatography (GC) methods, the presence of various mycotoxins (expressed for 12% of moisture content) was proved in 57.6% of all samples; mostly deoxynivalenol (DON, 54.5%) in concentrations of 130-2860 ?g/kg, followed by zearalenone (ZON, 15.1%, 70-800 ?g/kg), fumonisin B1 (3%, 120-210 ?g/kg), while fumonisin B2, ochratoxin A, diacetoxyscirpenol (DAS), HT-2 and T-2 toxins were not detected. The results indicate that further control of toxigenic moulds and mycotoxins in Slovenian primary grain production is thus required and justified.